Increased IL‐37 in Atherosclerotic Disease could be Suppressed by Atorvastatin Therapy. (10th September 2015) - Shaoyuan, C.; Ming, D.; Yulang, H.; Hongcheng, F.
Abstract Recently, the evidence showed that interleukin‐37 (IL‐37) was expressed in the foam‐like cells of atherosclerotic coronary and carotid artery plaques in IL‐37‐transgenic mice, suggesting that interleukin‐37 is involved in atherosclerosis‐related diseases. The purpose of this study was to determine the change of IL‐37 in atherosclerotic plaque, the effect of atorvastatin on IL‐37 and the association between IL‐37 and Smad3 in atherosclerotic disease. Rabbits were subjected to atherosclerosis by the immunologic injury composite with balloon injury (BI). Some rabbits received atorvastatin treatment from 6 weeks to 12 weeks. Serum levels of IL‐37 were assessed at baseline, 6 weeks and 12 weeks in normal, atherosclerotic and atorvastatin groups. Protein and RNA levels of IL‐37 atherosclerotic plaque from abdominal aorta were processed at 12 weeks. Abdominal aorta including atherosclerotic plaque was immunostained with IL‐37 and Smad3. Serum IL‐37 significantly increased in atherosclerotic disease, and this increase could be reduced by the atorvastatin treatment. IL‐37 and Smad3 were accumulated in the macrophage‐derived foam cells in the plaque and significantly increased in protein and RNA levels. Atorvastatin treatment could significantly suppress the increase of both IL‐37 and Smad3. Plasma level of IL‐37 and the IL‐37 expression of the plaque were significantly increased in atherosclerotic disease. This increase could be suppressed by the atorvastatin treatment. In addition, Smad3 might be required for IL‐37 activity during the atherosclerotic physiologic process.